Item Layout for Building Materials Management with Apriori Algorithm - Afrina Wati (Journal of Computer Scine and Information Technology, 2022)
The initial stage of opening a business is one of the business activities that can have an impact on the economy. TB. Jasa Manis is a trading business that sells various kinds of building materials, electrical equipment, materials and others. A sales strategy is needed to maintain business and marketing. Data Mining answers this problem by analyzing customer transaction data, then creating a certain rule, pattern or model. Products that are frequently purchased by customers will be used as a reference point in viewing consumer spending patterns. The association technique that can be used is an a priori algorithm designed to find item combinations. The a priori algorithm is guided by the min support and min confidence values. The combination pattern of sales transaction data itemset for two months on TB. Jasa Manis, it can be found that with a combination pattern the minimum support value is 14% and the minimum confidence is 40%. The rules for the highest association or goods that are often purchased together by customers are found in the Lotus Geese/LBR and Roof Nails. Through the analysis of customer shopping habits obtained, the layout of building materials can be adjusted to the customer's shopping pattern. With the data mining socialization rules, patterns of consumer shopping behavior can be identified and can increase sales at TB. Sweet Service